THE ROLE OF THE BANGKA JAYA BEACH TOURISM OBJECT IN INCREASING THE ECONOMIC GROWTH OF THE KRUENG GEUKUH COMMUNITY DEWANTARA DISTRICT NORTH ACEH REGENCY - Sutriani; Likdanawati; Jumadiah; Hamdiah (RADJA PUBLIKA, 2023)
This study aims to see how the Bangka Jaya Beach tourism object can have an impact on the economic growth of the community. In tourism the interaction between tourists and local communities can increase economic activities such as income, business opportunities, employment opportunities and reduce unemployment or poverty. Tourism is a driving force for the creation of community creativity in an effort to improve living standards. Efforts made to explore tourism potential can be in the form of developing human resources, implementation steps, as well as improving facilities and infrastructure, and human behavior towards the environment. This can boost the high interest of tourists to visit tourist destinations so that not only the community's economy grows.